CLINICAL OUTCOMES AND PROGNOSTIC FACTORS IN BREAST CANCER PATIENTS: A COMPARATIVE ANALYSIS (World Conference on Engineering and Technological Sciences, 2026)
Breast cancer remains one of the leading causes of cancer-related morbidity and mortality among women worldwide. Despite significant progress in early detection and treatment strategies, clinical outcomes vary considerably depending on tumor biology, stage at diagnosis, and patient-related factors. Identification of reliable prognostic indicators is essential for predicting disease progression, guiding treatment decisions, and improving survival outcomes.Prognostic factors in breast cancer include tumor size, lymph node involvement, histological grade, molecular subtype, hormone receptor status, HER2 expression, and proliferation markers such as Ki-67. In addition, patient-related characteristics such as age, menopausal status, comorbidities, and treatment adherence significantly influence therapeutic response and long-term survival.In transitional healthcare systems, late-stage diagnosis and limited access to advanced molecular testing may negatively affect prognosis. Comparative evaluation of clinical outcomes across different patient subgroups provides valuable insights into survival patterns and risk stratification.
Keywords: Breast cancer; clinical outcomes; prognostic factors; survival rate; tumor stage; lymph node involvement; molecular subtype; hormone receptor status; HER2; oncology management.